2015
DOI: 10.1097/acm.0000000000000500
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Internal Medicine Residency Graduate Performance on the ABIM Certifying Examination, Yearly In-Service Training Examinations, and the USMLE Step 1 Examination

Abstract: USMLE Step 1 and ITE scores have a modest correlation with board scores. Failing Step 1 or scoring in the bottom quartile of the ITE increased the risk of failing the boards. What effective intervention, if any, program directors may use with at-risk residents is a question deserving further research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 25 publications
2
65
0
Order By: Relevance
“…Prior studies have shown that internal medicine in-training examination scores predict certification examination scores. [26][27][28] However, in one study, A full unit change in the resident annual evaluation summary score is equivalent to a 0.5 unit change on the milestone score. b Regression-adjusted changes mean milestone ratings across program years is a significantly different change in the mean resident annual evaluation summary (RAES) ratings (P < .001).…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have shown that internal medicine in-training examination scores predict certification examination scores. [26][27][28] However, in one study, A full unit change in the resident annual evaluation summary score is equivalent to a 0.5 unit change on the milestone score. b Regression-adjusted changes mean milestone ratings across program years is a significantly different change in the mean resident annual evaluation summary (RAES) ratings (P < .001).…”
Section: Discussionmentioning
confidence: 99%
“…There was very high correlation between service examination scores. 26 In cases where more than one was present, we used the average score. We examined the relationships between in-service scores and the quality of feedback and between the polarity (positive, negative, neutral) of feedback in the seven domains and in-service examination scores using analysis of variance.…”
Section: Methodsmentioning
confidence: 99%
“…Those students meeting certain academic and professional criteria are offered an interview. USMLE Step 1 scores correlate with how well a student will do on a residency board exam (Kay, Jackson, & Frank, 2015). A primary goal of medical educators is to promote success for students and to help them fulfill their career ambitions.…”
Section: Introductionmentioning
confidence: 99%